2019
DOI: 10.1016/j.jtho.2019.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Web-Based Patient-Reported Outcome Surveillance in Patients With Lung Cancer

Abstract: Introduction: A multicenter randomized clinical trial in France found an overall survival benefit of web-based patient-reported outcome (PRO)-based surveillance after initial treatment for lung cancer compared with conventional surveillance. The aim of this study was to assess the cost-effectiveness of this PRO-based surveillance in lung cancer patients.Methods: This medico-economic analysis used data from the clinical trial, augmented by abstracted chart data and costs of consultations, imaging, transportatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 25 publications
2
83
0
Order By: Relevance
“…Again, perceived resource use was minimal, with a mean of 15 min weekly spent by the oncologist to manage all web alerts (n = 60 simultaneous users). Moreover, this study was the first to evaluate cost-effectiveness of an ePROM-based symptom monitoring approach (average annual cost €362 lower per patient in the ePROM arm; €20,912 total cost per Quality Adjusted Life Year) [40]. Both the STAR and e-FAP systems appeared to facilitate early detection of symptom deterioration and supportive care needs, improving patient outcomes and offering health provider/societal cost savings.…”
Section: Discussionmentioning
confidence: 97%
“…Again, perceived resource use was minimal, with a mean of 15 min weekly spent by the oncologist to manage all web alerts (n = 60 simultaneous users). Moreover, this study was the first to evaluate cost-effectiveness of an ePROM-based symptom monitoring approach (average annual cost €362 lower per patient in the ePROM arm; €20,912 total cost per Quality Adjusted Life Year) [40]. Both the STAR and e-FAP systems appeared to facilitate early detection of symptom deterioration and supportive care needs, improving patient outcomes and offering health provider/societal cost savings.…”
Section: Discussionmentioning
confidence: 97%
“…37,38 This group also analyzed the cost-effectiveness of their online strategy and found that the average annual cost of surveillance follow-up was €362 less per patient in the PRO arm (€941/year/patient) compared with the cost per patient in the control group (€1,304/year/patient). 39 The PRO approach showed an incremental cost-effectiveness ratio of €12,127 per life-year gained and €20,912 per quality-adjusted life-year gained. 39 Although the reason for longer survival in patients assigned to the electronic PRO approaches is unclear, the advantage might be explained by the convenience and speed with which patients received responses after reporting symptoms online.…”
Section: Electronic Patient-reported Outcome Reporting and Interventionmentioning
confidence: 98%
“…39 The PRO approach showed an incremental cost-effectiveness ratio of €12,127 per life-year gained and €20,912 per quality-adjusted life-year gained. 39 Although the reason for longer survival in patients assigned to the electronic PRO approaches is unclear, the advantage might be explained by the convenience and speed with which patients received responses after reporting symptoms online. Studies have indicated that at least 75% of lung cancer relapses are symptomatic 40 ; that some symptoms are predictive in shaping the clinical course and survival 23 ; and that intensive follow-up tends to improve survival.…”
Section: Electronic Patient-reported Outcome Reporting and Interventionmentioning
confidence: 98%
“…Patient-reported outcomes (PROs) consist of health-related questionnaires filled by the patients themselves, which can capture symptoms and signs and their severity. Scheduled electronic (e) PROs have many advantages compared to paper questionnaires such as reducing timely and locational limitations and offering a continuous collection of symptoms in a cost-effective manner [135][136][137]. The addition of ePRO to standard follow-up has been shown to improve survival and QoL of cancer patients treated with chemotherapy [138,139], but at present, there is only limited retrospective data on ePRO follow-up of cancer patients receiving ICIs [140], even though some prospective trials are ongoing.…”
Section: Controlling Treatment-related Side-effects Of Icismentioning
confidence: 99%